FAKTOR PENGARUH KEJADIAN ABORTUS SPONTAN PADA IBU HAMIL DI RSUD BANYUMAS TAHUN 2010 - Rina Prihastuti; Maya Safitri (Universitas Harapan Bangsa Purwokerto, 2010)
Mother Mortality in the World as well as in developing countries is stillhigh, one of which is caused by factors such as the direct cause of abortion 30-35%.The incidence of spontaneous abortion in hospitals Banyumas an increase from 195cases in 2009 to 379 cases in 2010. To find out the description of the factors thatinfluence the incidence of spontaneous abortion in pregnant women in BanyumasGeneral Hospital in 2010. This study was descriptive quantitative study with a retrospective approach.Type of data using secondary data. The population in this study were 379, thesampling techniques using total sampling, research instruments using the mastertable and the data analysis by univariate analysis. Spontaneous abortion in Banyumas General Hospital in 2010 as many as379 people (15.56%). Based spontaneous abortion maternal age the highest in theage group of 20-35 years as many as 161 people (42.5%) and the lowest in the agegroup <20 years of which 82 (21.6%). Based on the highest maternal parity paritymultiparas that 136 people (35.9%), and lowest in primiparous parity ie 64 (16.9%).Based on the history of abortion, which have a greater risk of spontaneous abortionin women who have a history of abortion are 193 people (50.9%). Spontaneous abortion by age of mother highest in the age group 20 to 35years as many as 161 people (42.5%), based on the highest maternal parity inmultiparas 136 people (35.9%) and those with greater risk of spontaneous abortionin women who have history of abortion that 193 people (50.9%).Keywords: Factors Influencing, Spontaneous Abortion.